2016
DOI: 10.1016/j.jiph.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Building predictive models for MERS-CoV infections using data mining techniques

Abstract: We believe that the performance of the prediction models can be enhanced with the use of more patient data. As future work, we plan to directly contact hospitals in Riyadh in order to collect more information related to patients with MERS-CoV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 5 publications
1
70
0
Order By: Relevance
“…Older age (65 years or over) was a major predictor of longer recovery delay in our sample. This was noted by Al‐Turaiki et al, as well . In other recent studies, being of older age was a factor for worse clinical outcomes such as infection severity and death in MERS‐CoV patients.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Older age (65 years or over) was a major predictor of longer recovery delay in our sample. This was noted by Al‐Turaiki et al, as well . In other recent studies, being of older age was a factor for worse clinical outcomes such as infection severity and death in MERS‐CoV patients.…”
Section: Discussionmentioning
confidence: 55%
“…As per the authors’ knowledge, two studies have so far addressed clinical improvement on laboratory‐confirmed MERS‐CoV patients . The first study, Shalhoub et al, was based on a case report in which their observations may not be generalized to a wider MERS‐CoV population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset consisted of 227 healthy newborns. Also in another study, Naive Bayes classifier and J48 decision tree algorithm were used for building predictive models for MERS-CoV infections Al-Turaiki et al (2016). The dataset used consists of 1082 records.…”
Section: Main Textmentioning
confidence: 99%
“…Recently, various types of data mining methods have been applied by a number of researchers [6,7], using real MERS-CoV datasets based on several types of machine learning classifiers. MERS is a complex disease caused by MERS-CoV that spreads easily and has a high death rate; approximately 40% of patients diagnosed with MERS have died [1].…”
Section: Introductionmentioning
confidence: 99%